The effect of minimalist shoe training on lower limb kinematics and kinetics in experienced shod runners - Schutte, Kurt Heinrich (Stellenbosch : Stellenbosch University, 2012)
Thesis (M Sport Sc)--Stellenbosch University, 2012.